2001
DOI: 10.1074/jbc.m009512200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Cartilage Oligomeric Matrix Protein Causing Pseudoachondroplasia and Multiple Epiphyseal Dysplasia Affect Binding of Calcium and Collagen I, II, and IX

Abstract: Mutations in type 3 repeats of cartilage oligomeric matrix protein (COMP) cause two skeletal dysplasias, pseudoachondroplasia (PSACH) and multiple epiphyseal dysplasia (MED). We expressed recombinant wildtype COMP that showed structural and functional properties identical to COMP isolated from cartilage. A fragment encompassing the eight type 3 repeats binds 14 calcium ions with moderate affinity and high cooperativity and presumably forms one large disulfidebonded folding unit. A recombinant PSACH mutant COMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
253
2
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(271 citation statements)
references
References 66 publications
12
253
2
4
Order By: Relevance
“…11,[58][59][60][61][62][63] Tolerability and toxicity must be carefully considered with long-term administration, whereas these factors are less important with short-duration therapies. Collectively, the observations reported here demonstrate that early ASO1 systemic administration dampens the MT-COMP growth plate chondrocyte phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[58][59][60][61][62][63] Tolerability and toxicity must be carefully considered with long-term administration, whereas these factors are less important with short-duration therapies. Collectively, the observations reported here demonstrate that early ASO1 systemic administration dampens the MT-COMP growth plate chondrocyte phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Functionally, COMP facilitates type II collagen fibril assembly, enhances chondrocyte attachment in vitro, and interacts with other ECM proteins, including type II and IX collagens, matrilin 3, and SPARC. [6][7][8][9][10][11][12] In contrast, mutations in COMP cause misfolding of the protein, preventing export from the chondrocyte and resulting in massive retention within the endoplasmic reticulum (ER). 10,[13][14][15] Although this finding has long been appreciated, there was little understanding of the pathologic molecular mechanisms, which are critical to develop mechanism-driven therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-two additional disease-linked mutations result in insertions or deletions of residues in the wire. Several examples of THBS-5 with mutations in the wire have been found to bind less calcium and to differ from wild-type THBS-5 in their stability and binding properties [47][48][49][50][51]. Thus, the sites of disease-causing mutations in THBS-5 target residues that appear to be critical for either the stability of the calcium-sensitive structure of the wire or the ability of the wire to stabilize the structure of the lectin-like module.…”
Section: Mapping Diseasementioning
confidence: 99%
“…These results suggested that calcium keeps the signature domains of THBSs in a more compact conformation that unravels when calcium is lost. In addition, the circular dichoic spectra changed with the removal or addition of calcium, indicating again that calcium causes a conformational change [44,48,60]. Interestingly, the circular dichroic spectrum of a THBS-2 construct comprising solely its wire repeats displays a calcium-dependent ellipticity minimum at 203 nm that is characteristic of the circular dichroic spectra of all THBSs studied to date [44].…”
Section: Effects Of Calciummentioning
confidence: 99%
“…After the collagen fibrils have formed, COMP dissociates from the mature fibril (9,10). It also interacts with a number of other extracellular matrix proteins, including matrilins (3), type IX collagen (11)(12)(13), and aggrecan (14).…”
mentioning
confidence: 99%